2022
DOI: 10.3389/fonc.2022.831506
|View full text |Cite
|
Sign up to set email alerts
|

NRAGE Confers Radiation Resistance in 2D and 3D Cell Culture and Poor Outcome in Patients With Esophageal Squamous Cell Carcinoma

Abstract: ObjectiveThe purpose of the study is to explore the mechanism of NRAGE enhancing radioresistance of esophageal squamous cell carcinoma (ESCC) in 2D and 3D levels.MethodsStably NRAGE-overexpressed ESCC cells and 3D-printing models for ESCC cells were established. Then, cellular malignancy indexes, such as cell morphology, proliferation, radioresistance, motility, apoptosis, cell cycle, and proteins of the Wnt/β-catenin pathway, were compared between radioresistant and its parental cells in 2D and 3D levels. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Fatty acid synthase was conformed contributes to epithelial-mesenchymal transition and invasion of SACC through PRRX1/Wnt/β-catenin pathway ( 32 ). The overactivation of Wnt/β-catenin signaling pathway was found be associated with radioresistance of cervical cancer and esophageal squamous cell carcinoma, while its role in SACC radioresistance is still unclear and more research is needed ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid synthase was conformed contributes to epithelial-mesenchymal transition and invasion of SACC through PRRX1/Wnt/β-catenin pathway ( 32 ). The overactivation of Wnt/β-catenin signaling pathway was found be associated with radioresistance of cervical cancer and esophageal squamous cell carcinoma, while its role in SACC radioresistance is still unclear and more research is needed ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of three biomarkers was detected by the IHC method as described in the instructions of ZSGB-BIO (PV-9000, Beijing, China). The immunohistochemical staining score was based on previously published articles ( 13 , 14 ). The staining estimation was assessed by the ImageJ software (National Institutes of Health).…”
Section: Methodsmentioning
confidence: 99%
“…NRAGE is a melanoma antigen-encoding gene homolog that interacts with neurotrophin-receptors to encode cancer-related proteins. Recent studies have confirmed that IR may promote NRAGE upregulation, which further triggers β-catenin nuclear protein accumulation, induces ESCC cell proliferation and cell cycle rearrangement, and then stimulates procancer activity [ 139 ]. Therefore, targeting the Wnt/β-catenin pathway is expected to result in prolonged OS and PFS in ESCC patients treated with IR, significantly improving prognosis.…”
Section: Reversal Strategy Of Escc Radioresistancementioning
confidence: 99%